2018
DOI: 10.1016/j.jfma.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Is quality of registry treatment data related to registrar experience and workload? A study of Taiwan cancer registry data

Abstract: The accuracy rate for the first course of cancer treatment was affected by the cancer type and the experience of cancer registrars, but it was not affected by the workload of cancer registrars. We recommend that cancer registrars with basic licenses upgrade to advanced licenses as soon as possible. Medical record collaboration should establish documentation for checklist of radiotherapy and surgical operation records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…According to Cancer Registry Annual Report published by Ministry of Health and Welfare, Taiwan in 2018 1 , the total number of patients diagnosed with melanoma during 1997–2012 was 3057, which was close to the cohort number of this study. The Taiwan Cancer Registry Annual Report was based on the Taiwan Cancer Registry database, which provides complete core information for cancer cases in Taiwan 17 , 18 .
Figure 1 Design and flowchart of patient selection.
…”
Section: Methodsmentioning
confidence: 99%
“…According to Cancer Registry Annual Report published by Ministry of Health and Welfare, Taiwan in 2018 1 , the total number of patients diagnosed with melanoma during 1997–2012 was 3057, which was close to the cohort number of this study. The Taiwan Cancer Registry Annual Report was based on the Taiwan Cancer Registry database, which provides complete core information for cancer cases in Taiwan 17 , 18 .
Figure 1 Design and flowchart of patient selection.
…”
Section: Methodsmentioning
confidence: 99%
“…The original data for our primary analysis were retrieved from the TCR database. The TCR provides complete core information for cancer cases in Taiwan that meet the criteria for high data quality [11, 12]. Its data source consists of 19 medical centers and a district hospital specializing in cancer research, Koo Foundation Sun Yat-Sen Cancer Center.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor grade, lymph vessel or vascular invasion, breast cancer subtype, and pathologic stage were categorical variables. Breast cancer subtypes were categorized as proposed by Blows [12] and Cheng [13], with grouping into three major subtypes: (1) luminal-like subtype (HR+ and HER2−), (2) HER2 subtype (HER2+), and (3) triple-negative subtype (HR− and HER2−). For tumor grade, 1 means the well differentiated or differentiated; 2 means moderately differentiated, moderately well differentiated, or intermediate differentiation; and 3 means poorly differentiated, dedifferentiated, undifferentiated, or anaplastic.…”
Section: Methodsmentioning
confidence: 99%
“…43 A previous validation study showed good accuracy in the details of radiotherapy and chemotherapy treatment. 44 Third, due to the lack of laboratory data and imaging data, we could not compare the biochemical failure survival between the IGRT and non-IGRT groups. However, this is not an obstacle for our primary endpoint, OS.…”
Section: Discussionmentioning
confidence: 99%